Use of cracked maize as a carrier for NDV4 vaccine in experimental vaccination of chickens - Nwankiti Obinna O; Echeonwu Georgebest ON; Ndako James A; Olabode Atanda O; Chukwuedo Anthony A (Virology Journal, 2010)
Abstract The suitability of V4 vaccine coated on cracked local grain (maize) and its husks and used for oral vaccination of chickens was assessed. Seventy-two (72) birds aged three (3) weeks and above were divided into six groups of twelve (12) birds per group. The birds were bled to determine their prevaccination HI antibody status while five different samples of cracked maize were coated with the V4 vaccine and fed to the chickens orally in each of the groups. All birds in the group including the controls were bled at 7, 14 and 21 days post vaccination to determine the presence and level of antibody response in each of the groups. Results obtained showed that prevaccination haemagglutination inhibition (HI) titre was less than two (log2) in 18% of the birds used in this experiment, however 14% of the birds had an HI titre of ≤ 4. The post vaccination antibody titre showed that birds vaccinated with vaccine coated maize gave a post vaccination HI antibody titre of between Log2(6-8). when the coated maize samples were soaked in water at room temperature and assessed after 24 hours, the treated maize parts gave >6.3 log10 EID50 and above while the untreated parts gave < 3.0 log10 EID50. The experiment showed that whole maize and husks, which were not treated, may contain agents which are virus inhibitory. Form this research the treated maize which was soaked and washed gave a higher geometric mean titre, hence tends to be good carriers of the virus (vaccine). It is therefore concluded from this work that processed cracked maize could be a good carrier of NDV4 vaccine. It is hereby recommended that only treated maize could be used as carrier for the V4 vaccine.